A case of Brown-Sequard syndrome with associated Horner's syndrome after blunt injury to the cervical spine. Issue 6 (1st November 2001) - Edwards, A; Andrews, R
Abstract : A 26 year old motorcyclist was received by the trauma team in our accident and emergency department after a head on collision with a motor vehicle. He had been correctly immobilised and his primary survey was essentially normal. He was alert and orientated with a Glasgow Coma score of 15 and had no symptoms or signs of spinal injury. His cervical spine radiography was also normal. Neurological examination however, revealed anisocoria, his left pupil being smaller than his right, and a Brown-Sequard syndrome, with a sensory level at C6. Immobilisation was maintained and he was transferred to the regional neurosurgical centre where magnetic resonance imaging revealed a contusion of the left half of the spinal cord adjacent to the 6th cervical vertebrae. Computed tomography revealed no bony injury but spinal column instability was demonstrated after flexion-extension spinal views and he underwent surgery to fuse his spine at the C5-C6 level. This report highlights the necessity to observe strict ATLS guidelines. This must include a thorough examination of the central and peripheral nervous system where spinal injury is suspected, even in the absence of radiographic abnormality and neck pain. This article also presents the unusual phenomena of Brown-Sequard syndrome and unilateral Horner's syndrome after blunt traumatic injury to the cervical spine.